Ecological Analysis of Stunting Toddlers in East Nusa Tenggara Province 2021 - Yulianti Nataya Rame Kana; Mohammad Zainal Fatah; Muji Sulistyowati (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
Stunting is a chronic condition that results in stunted growth of children under five due to malnutrition for a long time. The objective of this study is to analyze the factors associated with the occurrence of stunting in East Nusa Tenggara Province in the year 2021. An ecological approach is employed in this study, utilizing secondary data obtained from the 2021 East Nusa Tenggara Province Health Profile report. This research was conducted from January to March 2023. Analysis was carried out on a total of 22 districts/cities, with a population of 388,760 toddlers which included the entire sample size, namely toddlers with stunting incidents totaling 81,354 toddlers. The main variable predicted is the proportion of stunted toddlers. Predictor variables consist of the percentage of ANC visits, the proportion of LBW history and the percentage of exclusive breastfeeding. Bivariate analysis involved the utilization of cross-tabulation to examine the relationships between variables. The results of the study show that the prevalence of stunting status in toddlers is in the moderate category (16.04-24.07%). This happened as the coverage of ANC visits in districts/cities was in the low category (40.0-61.6%), history of LBW in districts/cities was in the low category (3.0-6.6%) and breastfeeding exclusively in districts/cities that are in the high category (65.67-93.0%). Stunting among toddlers in the province of East Nusa Tenggara in 2021 is in the moderate category along with ANC visits in districts/cities which are in the low category, history of LBW in districts/cities is in the low category and exclusive breastfeeding in districts/cities is also in the low category. To accelerate stunting prevention in Indonesia, it is essential to have synchronized efforts in planning, implementation, and monitoring at all government levels, including villages. The active involvement of all stakeholders is crucial in achieving this goal. Keyword: Community nutrition, Ecological analysis, Secondary data, Stuned